2014
DOI: 10.3402/gha.v7.24939
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the impact of the JSY cash transfer program on maternal mortality reduction in Madhya Pradesh, India

Abstract: BackgroundThe Indian Janani Suraksha Yojana (JSY) program is a demand-side program in which the state pays women a cash incentive to deliver in an institution, with the aim of reducing maternal mortality. The JSY has had 54 million beneficiaries since inception 7 years ago. Although a number of studies have demonstrated the effect of JSY on coverage, few have examined the direct impact of the program on maternal mortality.ObjectiveTo study the impact of JSY on maternal mortality in Madhya Pradesh (MP), one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 23 publications
0
52
1
Order By: Relevance
“…Rates of institutional delivery have more than doubled since the advent of National Rural Health Mission (NRHM), and currently more than 74 % of total births in India are occurring at institutions [13]. However, various studies have failed to show a commensurate reduction in maternal and neonatal mortality [14, 15]. Thus, just having a contact with the health system for deliveries has not proven to be enough for improving outcomes, which suggests a need to focus on the quality of care during these contacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of institutional delivery have more than doubled since the advent of National Rural Health Mission (NRHM), and currently more than 74 % of total births in India are occurring at institutions [13]. However, various studies have failed to show a commensurate reduction in maternal and neonatal mortality [14, 15]. Thus, just having a contact with the health system for deliveries has not proven to be enough for improving outcomes, which suggests a need to focus on the quality of care during these contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, just having a contact with the health system for deliveries has not proven to be enough for improving outcomes, which suggests a need to focus on the quality of care during these contacts. Experience from JSY also indicates that while the focus on bringing women to institutions may have influenced the first and second delay in care, the third delay, i.e., in timely and high-quality care provision at institutions is still a challenge [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also reported that the poor availability of laboratory facilities and diagnostic equipment are also obstacles to patient assessment and diagnosis, even when providers are aware of the necessary tests [32]. India learned this with Janani Suraksha Yojana, a cash incentive programme for facility births, which massively increased facility delivery but did not measurably reduce maternal or newborn mortality [33]. High-quality care is determined by thorough assessment, detection of asymptomatic and co-existing conditions, precise diagnosis, proper and timely treatment, referral when needed for hospital care and surgery, and the ability to follow the patient and regulate the treatment course as needed.…”
Section: Discussionmentioning
confidence: 99%
“…This programme has been instrumental in the gains achieved by the recent conditional cash transfer programme, Janani Suraksha Yojana (JSY), to enhance facility based births 36. The uptake of the JSY programme has been varied but it has been associated with a reduction of 3.7 perinatal deaths per 1000 pregnancies and 2.3 neonatal deaths per 1000 livebirths 37…”
Section: Community Based Models To Tackle Inequitiesmentioning
confidence: 99%